Fluorescent probes and delivery methods for single-molecule experiments - Lymperopoulos, Konstantinos; Kiel, Alexander; Unger, Anne Lucia Katharina; Stöhr, Katharina; Herten, Dirk-Peter (ChemPhysChem, 2010)
The recent explosion in papers utilising single-molecule experiments pushes the envelope further for increased spatial and temporal resolution. In order to achieve this, a combination of novel fluorescent probes and spectroscopy techniques are required. Herein, we provide an overview on our contribution to developments in the field of fluorescent probes along with a palette of alternative delivery methods for introducing the probes into living cells. We discuss probe requirements arising from the use of single-molecule spectroscopy methods and the customisation of probes that depends on the target molecule, the chemical state of the molecule as well as the distance and the type of interaction between sensor and ligand. We explain how Förster resonance energy transfer (FRET) and photon-induced electron transfer (PET) can increase the probe customisation. We also discuss additional requirements that arise when performing experiments in living cells like toxicity and cell permeability. Regarding the latter, we devote a special paragraph on the different ways to introduce the desired probe into the cell and how the different properties of each probe and cell type may require different delivery methods. We offer insights based on our experience working with a variety of single-molecule methods, fluorescent probes and delivery systems. Overall, we encompass the latest developments on probe design and delivery and illustrate that the wealth of information provided by single-molecule studies goes along with increased complexity.
Online veröffentlicht am 4. Dezember 2009
Gesehen am 20.04.2023